O godności w polityce - Suchocka, Hanna (Horyzonty Wychowania, 2017)
Looking for the link between dignity and politics, the author quotes popular encyclopaedic definitions, which suggest that an obvious aim of every political action is gaining or keeping power. And since the aim of political authority should be serving the general good, decisions made by politicians should be based on values identifying the rights of individual citizens. The best protection for these rights is respecting the natural law, however in many countries binding regulations do not refer to this basic norm directly. Therefore, dignity is not always treated as a fundamental characteristic of every human being, though usually politics assumes concern for citizens’ dignity, their decent life etc. In Polish political experiences of the second half of the 20th century the principle of solidarity had an important position, as the opposite of the principle of class hatred (class struggle) the communists subscribed to. Solidarity, chosen as the motto by a huge social movement, was a protest against indecent living conditions, and at the same time striving after practising decent politics, i.e. honest and based on the truth.